2020
DOI: 10.1080/00480169.2020.1745109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of treatment of phantom cows with a progesterone-based synchrony programme

Abstract: ANOVA tests of nested models with and without the variable are in bold, otherwise the p-values are Wald tests. cFriesian was defined as a cow ≥12/16 Friesian.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The economic return of phantom cow intervention was unsurprisingly highly dependent on the sensitivity of veterinary pregnancy diagnosis. A previous study in seasonal-calving Australian dairy herds estimated the sensitivity of ultrasonographic pregnancy diagnosis at 93.9% at a minimum of 35 d postinsemination (Shephard and Morton, 2018) and in the randomized controlled trial upon which the present study is based, the sensitivity of pregnancy diagnosis was not estimated, but we found that 7/189 (4%) phantom cows allocated to the control group were ≥35 d pregnant at the initial pregnancy diagnosis (Chambers et al, 2020). Although both of these studies found sensitivities below the 99.2% needed to achieve the economic break-even for phantom cow intervention, it is worth noting another study in non-seasonal-calving North American dairy cows found that the sensitivity of transrectal ultrasonography for diagnosing pregnancy increased from 74.5% at d 24 postinsemination to 100% at d 29 postinsemination (Romano et al, 2006).…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…The economic return of phantom cow intervention was unsurprisingly highly dependent on the sensitivity of veterinary pregnancy diagnosis. A previous study in seasonal-calving Australian dairy herds estimated the sensitivity of ultrasonographic pregnancy diagnosis at 93.9% at a minimum of 35 d postinsemination (Shephard and Morton, 2018) and in the randomized controlled trial upon which the present study is based, the sensitivity of pregnancy diagnosis was not estimated, but we found that 7/189 (4%) phantom cows allocated to the control group were ≥35 d pregnant at the initial pregnancy diagnosis (Chambers et al, 2020). Although both of these studies found sensitivities below the 99.2% needed to achieve the economic break-even for phantom cow intervention, it is worth noting another study in non-seasonal-calving North American dairy cows found that the sensitivity of transrectal ultrasonography for diagnosing pregnancy increased from 74.5% at d 24 postinsemination to 100% at d 29 postinsemination (Romano et al, 2006).…”
Section: Discussionmentioning
confidence: 62%
“…Treating these cows with synchrony programs that abort pregnancy is likely to lead to significant economic costs given their reduced chance of re-conceiving by the end of mating, the delayed calving date if they re-conceive and resulting shorter lactation in the next season, and the potential loss of a valuable, AI-bred calf. In the previous randomized controlled trial, 5.8% of cows in the control group were subsequently determined to have been <35 d pregnant at the initial pregnancy diagnosis (status B; Chambers et al, 2020). Similarly, Cuttance and Mason (2015) found 6.4% of cows diagnosed as phantom cows were subsequently confirmed to have been <35 d pregnant at enrolment.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations